Probiotic Potential and Safety Properties of Lactobacillus plantarum from Slovak Bryndza Cheese. (4th September 2013) - Belicová, Anna; Mikulášová, Mária; Dušinský, Roman
Abstract : One hundred and twenty-five acid-resistant presumptive lactobacilli were isolated from Slovak Bryndza cheese and screened for their antimicrobial activity against eight bacterial pathogens using spot agar assay. Out of twenty-six Lactobacillus strains with strong inhibition activity, twenty were identified as Lactobacillus plantarum and six as Lactobacillus fermentum . The most active eleven L. plantarum isolates were further characterized in vitro for some probiotic and safety properties. Only three isolates K10, K21, and ZS07 showed the ability to grow over 50% in the presence of 0.3% bile. Strong deconjugation efficiency was determined for CK06 and K21. The highest β -galactosidase activity was shown in isolates ZS11, B01, CK06, and ZS07. Only three of the strains had the ability to produce tyramine: CK06, LM1, and ZS11. Strains K09, K21, ZS11, and ZS15 were susceptible to all tested antibiotics. Analysis of the results confirmed the L. plantarum isolates ZS07 and K21 as the most suitable for probiotic use, due to their desirable probiotic and safety characteristics.